2021
DOI: 10.2147/ott.s288799
|View full text |Cite
|
Sign up to set email alerts
|

KDM5C Expedites Lung Cancer Growth and Metastasis Through Epigenetic Regulation of MicroRNA-133a

Abstract: Background KDM5C, a histone H3K4-specific demethylase, possess various biological functions in development of cancers. However, its relation to the microRNA (miRNA) regulation in lung cancer remains unknown. This study aims to study the regulatory role of KDM5C on modification of miR-133a in the progression of lung cancer. Methods Differentially expressed miRNAs were filtered from 34 paired lung cancer and paracancerous tissues. The correlation between miR-133a expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…32 It has been revealed that KDM5C mediate miR-133a expression to suppress development and metastases of lung cancer by targeting PTBP1. 33 Across these databases, we consistently observed elevated expression levels of KDM5B/C and relatively high gene mutations in either LUAD or LUSC, which remind us of their oncogenic properties under cancer type-specific context.…”
Section: Dovepressmentioning
confidence: 62%
“…32 It has been revealed that KDM5C mediate miR-133a expression to suppress development and metastases of lung cancer by targeting PTBP1. 33 Across these databases, we consistently observed elevated expression levels of KDM5B/C and relatively high gene mutations in either LUAD or LUSC, which remind us of their oncogenic properties under cancer type-specific context.…”
Section: Dovepressmentioning
confidence: 62%
“…Several key methyltransferases and demethylases, such as SETDB1, EZH2, ASH1L, WHSC1, NSD1, EHMT2, KDM1A, KDM3A, KDM3B, KDM4B, and KDM5B, have been demonstrated to be frequently upregulated in HCC tumor tissues and possibly implicated in its pathogenesis 20–22 . KDM5C has been suggested as a pan‐cancer‐driver 11 and reportedly involved in the tumorigenesis of cancers of the colon, 12 stomach, 23 and lung 24 . Importantly, KDM5C has also been reported to augment migration, invasion and epithelial–mesenchymal transition of HCC cells 13 .…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] KDM5C has been suggested as a pan-cancer-driver 11 and reportedly involved in the tumorigenesis of cancers of the colon, 12 stomach, 23 and lung. 24 Importantly, KDM5C has also been reported to augment migration, invasion and epithelial-mesenchymal transition of HCC cells. 13 In the present study, data from publicly accessible databases suggested that KDM5C was highly expressed in LIHC and indicated poor patient prognosis, and high-expression profiling of KDM5C was confirmed in LIHC cell lines.…”
Section: Downregulation Of Kdm5c Inhibits Growth Of Lihc Xenograft Tu...mentioning
confidence: 99%
“…It promotes breast cancer tumorigenesis by activating ERα-target genes or repressing BRMS1 expression and protects breast cancer cells from immune surveillance by repressing type I interferons and interferon-stimulated genes [36,142]. KDM5C also plays oncogenic roles in gastric cancer, colon cancer, hepatocellular carcinoma, and lung cancer by suppressing p53, FBXW7, BMP7, and miR-133a, respectively [143][144][145][146].…”
Section: Kdm5cmentioning
confidence: 99%